Antibacterial Activity of Pare Fruit (Momordica Charantia L.) Against Bacteria Staphylococus Aureus - Muhammad Alviyan Shutiawan; Ismi Rahmawati; Opstaria Saptarini (MultiTech Publisher, 2023)
Bitter Gourd Fruit (Momordica charantia L). contains alkaloids, flavonoids, saponins, tannins and terpenoids. The compounds contained in bitter melon have anti-biofilm activity. Biofilm is a collection of microorganisms that stick to the surface of objects and form a matrix. This research aims to determine the potential of the active fraction of n-hexane, ethyl acetate and water in antibacterial and biofilm activity in the form of inhibiting biofilm formation, biofilm degradation, bacteria S. Aureus Bitter melon fruit was extracted using the maceration method with 96% ethanol solvent. The thick extract was then fractionated using n-hexane, ethyl acetate and water as solvents.